2014
DOI: 10.12691/ajcp-2-2-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IHC, FISH, ER and PR in Breast Cancer in Western Iran

Abstract: To evaluate the concordance and discordance between IHC and FISH results for detection of Her2/neu protein, analyses of ER and PR, and also evaluation of the benefit of adjuvant trastuzumab in patients diagnosed with human epidermal growth factor receptor 2 (HER2) -positive invasive ductal carcinoma enrolled onto the Herceptin adjuvant. IHC analysis of ER, PR and HER2 was performed in 133 patients of breast cancer with invasive ductal carcinoma. 90(67.6%) cases were confirmed by FISH. Statistical analysis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
(33 reference statements)
0
8
3
Order By: Relevance
“…Studies from Iran, Taiwan, and Switzerland reported concordance of 81.2%, 83% and 84% and discordance of 18.7%, 16.7% and 16% in cases with IHC staining 3+ and Her-2/neu FISH, respectively. 12,15,20 Studies from India showed concordance of 78% and 85% and discordance of 21.8% and 14.2%, respectively which is in stark contrast to current study. 6,13 A local study and studies from America, Iran, and Saudi Arabia reported concordance rate of 74%, 69%, 61.5% and 50%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Studies from Iran, Taiwan, and Switzerland reported concordance of 81.2%, 83% and 84% and discordance of 18.7%, 16.7% and 16% in cases with IHC staining 3+ and Her-2/neu FISH, respectively. 12,15,20 Studies from India showed concordance of 78% and 85% and discordance of 21.8% and 14.2%, respectively which is in stark contrast to current study. 6,13 A local study and studies from America, Iran, and Saudi Arabia reported concordance rate of 74%, 69%, 61.5% and 50%, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…12,13 Studies from Switzerland, America, Spain and Iran reported gene amplification in 95%, 7.1%, 18%, and 32.4% cases while gene was not amplified in 5%, 88%, 81%, and 67.6% cases, respectively. 15,16,20,21 Studies from Turkey, Iran, and Saudi Arabia showed 23%, 27.9% and 23% and gene amplification in cases scoring 2+ immunostaining. 7,14,19 Concordance between IHC scoring 3+ and Her-2/neu gene in Indian studies, 17,18 was 93.9% and 92.9% and discordance of 3.65% and 7.1% between IHC scoring 3+ and Her-2/neu FISH, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Dieci et al ( 16 ) investigated 480 breast cancer tissues with 2+ HER2, revealing that high tumor grade and high Ki67 were significantly associated with HER2 FISH amplification. Payandeh et al ( 17 ) recruited females with breast cancer at the Oncology Clinic, Kermanshah, Iran. Of the 133 patients, 37 were classified as IHC 2+ and 96 were classified as IHC 3+.…”
Section: Discussionmentioning
confidence: 99%
“…Patients diagnosed to have infiltrating ductal carcinoma (Figure 1a) were 20 (58.82%), those with infiltrating lobular carcinoma were 13 ER status analysis showed 13 (38.24%) patients as ER-positive, and 21 (61.76%) were ER-negative. PR positive status was seen in 11 (32.35%), and PR negative was 23 (67.65%).…”
Section: Resultsmentioning
confidence: 99%